Comparative Study of Functional Monomers and Crosslinkers in the Synthesis of Molecularly Imprinted Polymers for Selective Removal of Bisphenol A - Lasmaryna Sirumapea; Tri Saputra Tambunan; Maharani Utami; Erjon; Arie Firdiawan; Fitria Puspita (Study Program of Chemistry, Faculty of Mathematics and Natural Sciences, Universitas Pakuan, 2026)
Bisphenol A (BPA) is an endocrine-disrupting compound associated with documented environmental and health risks. This study evaluates and compares two distinct Molecularly Imprinted Polymer (MIP) architectures synthesized via bulk polymerization for selective BPA adsorption. System A utilized Methacrylic Acid (MAA) crosslinked with Ethylene Glycol Dimethacrylate (EGDMA), while System B employed Acrylamide (AM) with Trimethylolpropane Trimethacrylate (TRIM). FTIR spectroscopy confirmed template-monomer hydrogen bonding, while SEM revealed a porous morphology for System A compared to the dense surface of System B. Batch adsorption results showed that System A achieved a higher maximum capacity (Qmax = 14.74 mg/g) and imprinting factor (IF = 7.96) than System B (Qmax = 9.1 mg/g; IF = 3.33). These findings are attributed to the hydrogen-bonding affinity of MAA and enhanced site accessibility within the EGDMA matrix. Conversely, System B exhibited a higher selectivity coefficient (α = 4.1) against paracetamol than System A (α = 3.04), reflecting the influence of TRIM-induced rigidity on cavity fidelity. These findings indicate that the AM-TRIM system provides higher selectivity, while the MAA-EGDMA system demonstrates higher adsorption capacity for potential environmental applications.